The power of Digital marketing - Influencers impact on purchase intention : A qualitative study among students at LTU - Hannu, David; Johannisson, Markus (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
The online revolution has developed digital marketing, and how businesses connect with new consumers. The commercial usage of the World Wide Web has created opportunities for businesses to market their product through new digital platforms and marketing strategies. Therefore, social media platforms such as Instagram has become a dominant communication channel for consumers. From a business perspective this has created an opportunity by marketing their product through influencer marketing. An influencer is a person who has built a social network with people following them on the social platforms. The influencer is getting paid to market products on their social media to influence their followers. 98% of people studying in Sweden are using social media frequently, this makes them a target group suited for influencer marketing. The purpose of this thesis is to evaluate how influencer marketing affect students’ attitudes and subsequently purchase intention through social media. To answer this research purpose a theoretical framework has been developed based on Theory of Reasoned Action. Semi structured interviews were conducted on a one-to-one basis with 17 students at Luleå University of Technology (LTU). The interviews focused on attitudes towards influencer marketing and subjective norms, and how these would subsequently affect their purchase intention. To analyze the interviews a thematic analysis was conducted. The data was coded based on observations of repetitive answers and themes, consisting of negative or positive attitudes towards influencers, as well as the impact of the subjective norms on the participants and how it affects their purchase intention. Results showed that there was an overall negative attitude towards influencers, that the subjective norms seem to have a significant and that purchase intention is mostly affected by the direct influence from the subjective norms. Analysis of these results leads to the conclusion that influencer marketing has a negative impact on students’ attitudes. On the ...